Essentialism and anti-essentialism in "The Evening and the Morning and the Night", by Octavia Butler - Cavalcanti, Ildney; De La Rocque, Lucia (Revista Leitura, 2019)
Despite the fact that feminist literary criticism can boast a much longer history than that of the feminist critique of science, both can be grouped under the umbrella term "gender studies" and are able to jointly illuminate certain issues related to questions of gender and science. In the present work, we propose to carry out a reading of Octavia Butler's "The evening and the morning and the night" which departs from these feminist battlegrounds, dealing with the opposite yet complementary viewpoints from the biological and social sciences. Special attention is given to the concept of essentialism, as Butler's work, in all its complexity, can both confirm and disrupt its precepts. DOI: 10.28998/0103-6858.2008v1n41p55-73